2021
DOI: 10.3892/mmr.2021.12313
|View full text |Cite
|
Sign up to set email alerts
|

Salusin‑β participates in high glucose‑induced HK‑2 cell ferroptosis in a Nrf‑2‑dependent manner

Abstract: Ferroptosis is critically involved in the pathophysiology of diabetic nephropathy (DN). As a bioactive peptide, salusin-β is abundantly expressed in the kidneys. However, it is unclear whether salusin-β participates in the pathologies of diabetic kidney damage by regulating ferroptosis. The present study found that high glucose (HG) treatment upregulated the protein expressions of salusin-β in a dose-and time-dependent manner. Genetic knockdown of salusin-β retarded, whereas overexpression of salusin-β aggrava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 68 publications
(91 reference statements)
0
18
0
Order By: Relevance
“…Different from the previously mentioned role of the NRF2 pathway, W. J. Wang et al. found salusin-β is involved in high glucose-induced ferroptosis of renal tubular cells HK-2 in an NRF2 dependent manner, indicating that salusin-β and ferroptosis form a positive feedback loop, which promotes high glucose-induced renal tubular cell injury [ 95 ]. However, this effect is only explored in cell experiments, and animal experiments are still needed for further research.…”
Section: Ferroptosis and Ferritinophagy Participate In The Pathogenes...mentioning
confidence: 86%
“…Different from the previously mentioned role of the NRF2 pathway, W. J. Wang et al. found salusin-β is involved in high glucose-induced ferroptosis of renal tubular cells HK-2 in an NRF2 dependent manner, indicating that salusin-β and ferroptosis form a positive feedback loop, which promotes high glucose-induced renal tubular cell injury [ 95 ]. However, this effect is only explored in cell experiments, and animal experiments are still needed for further research.…”
Section: Ferroptosis and Ferritinophagy Participate In The Pathogenes...mentioning
confidence: 86%
“…Renal tubular injury is a critical factor in DKD. High glucose (HG) triggered iron overload, antioxidant capability reduction, massive ROS production, and lipid peroxidation in renal tubular cell death ( 23 , 88 ). Salusin−β, a bioactive peptide of 20 amino acids, participates in HG−induced HK−2 cell ferroptosis in an Nrf−2−dependent manner ( 88 ).…”
Section: Effects and The Molecular Mechanisms Of Ferroptosis On Diabe...mentioning
confidence: 99%
“…It is worth noting that "ferroptosis" named in 2012 (Dixon et al, 2012) is appreciated as one of the most widespread and ancient forms of cell death, because of the similarity to ferroptosis-like cell death observed in evolutionarily remote species, such as plants protozoa and so on (Distefano et al, 2017;Bogacz and Krauth-Siegel, 2018). Previous studies have observed the existence of ferroptosis in renal tubules in DN Wang et al, 2021), but which in glomerulus and its mechanism still need to be further explored.…”
Section: Introductionmentioning
confidence: 99%